2018
DOI: 10.1021/acs.est.8b03241
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Soil Concentration for VOC-Contaminated Site Assessments Explored Using Field Data from the Beijing-Tianjin-Hebei Urban Agglomeration

Abstract: A total of 128 available soil−soil gas data pairs of benzene were collected from 5 contaminated sites in the Beijing-Tianjin-Hebei urban agglomeration. Soil gas concentrations predicted by the linear model and the dual equilibrium desorption (DED) model were compared with measured values. Although the immersion of soil samples in methanol during sampling and preservation was specified to minimize volatilization losses and biodegradation, the study still found that many points with high soil gas concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Using current standard laboratory analytical methods for determination of VOCs, such as USEPA Methods TO-14 and TO-15 (Method TO-17, 1999;Compendium Method TO-15, 1997), requires collection of the samples with specified containers and their transport to a laboratory for analysis. Alternatively, soil gas sampling was finished by purging soil gas to sorbent tube to absorb target VOCs, then the sealed sorbent tubes were sent back to the laboratory to desorption with solvent and test with GC-MS (Zhang et al, 2019). These laboratories are typically equipped with the most sensitive equipment and the analysis for VOCs carries with it high costs and lengthy timeframes.…”
Section: Introductionmentioning
confidence: 99%
“…Using current standard laboratory analytical methods for determination of VOCs, such as USEPA Methods TO-14 and TO-15 (Method TO-17, 1999;Compendium Method TO-15, 1997), requires collection of the samples with specified containers and their transport to a laboratory for analysis. Alternatively, soil gas sampling was finished by purging soil gas to sorbent tube to absorb target VOCs, then the sealed sorbent tubes were sent back to the laboratory to desorption with solvent and test with GC-MS (Zhang et al, 2019). These laboratories are typically equipped with the most sensitive equipment and the analysis for VOCs carries with it high costs and lengthy timeframes.…”
Section: Introductionmentioning
confidence: 99%
“…The authors are not aware of any field studies that clearly show meaningful correlations between paired VOC concentrations in soil and soil gas (Ma ). In particular, benzene has been observed at very high concentrations in soil gas (>2000 μg/m 3 ) where corresponding soil concentrations are below detection limits (Zhang et al ). VOC vapor concentrations can also be orders of magnitude less than those predicted based on soil concentrations and equilibrium vapor partitioning relations (Golder‐Associates ).…”
Section: Rationale For Soil‐gas Sampling For VI Risk Assessmentmentioning
confidence: 99%
“…Although the sampling and analysis methods for these media are relatively mature, they still face problems such as sample container contamination , and several other challenges (see section ). Note that soil sampling, which currently provides the most important evidence for site risk assessment and decision making in China, ,, is generally not recommended for VI assessment based on USA’s experiences, , since no studies reported meaningful correlations between paired VOC concentrations in soil and soil gas and volatilization loss of VOCs is difficult to avoid during soil sampling. ,, …”
Section: Vapor Intrusion Investigation Toolsmentioning
confidence: 99%
“…Note that soil sampling, which currently provides the most important evidence for site risk assessment and decision making in China, 1,113,114 is generally not recommended for VI assessment based on USA's experiences, 113,114 since no studies reported meaningful correlations between paired VOC concentrations in soil and soil gas and volatilization loss of VOCs is difficult to avoid during soil sampling. 113,115,116 4.2. Innovative Investigation Techniques.…”
Section: Vapor Intrusion Investigation Toolsmentioning
confidence: 99%